2020
DOI: 10.1177/1742271x20971323
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound grading of thyroid nodules using the BTA U-scoring guidelines – Is there evidence of intra-and interobserver variability?

Abstract: Introduction U-score ultrasound classification (graded U1-U5) is widely used to grade thyroid nodules based on benign and malignant sonographic features. It is well established that ultrasound is an operator-dependent imaging modality and thus more susceptible to subjective variances between operators when using imaging-based scoring systems. We aimed to assess whether there is any intra- or interobserver variability when U-scoring thyroid nodules and whether previous thyroid ultrasound experience has an effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Although the level of agreement for the U-categories was only fair ( K = 0.21) in the department, this appears in line with the study conducted by Couzins et al 12 where the agreement for the experienced group was of K = 0.24–0.34. This, however, is significantly lower from the one reported by Weller et al 11 ( K = 0.73).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although the level of agreement for the U-categories was only fair ( K = 0.21) in the department, this appears in line with the study conducted by Couzins et al 12 where the agreement for the experienced group was of K = 0.24–0.34. This, however, is significantly lower from the one reported by Weller et al 11 ( K = 0.73).…”
Section: Discussionsupporting
confidence: 89%
“…Couzins et al, 12 on the contrary, studied the inter- and intra-operator reliability on 20 TNs between 14 US operators with different experience. Although no statistically significant variability existed when U-scoring, the study demonstrated only slight to fair agreement between all the participants and within the experienced group only ( K = 0.19–0.34).…”
Section: Introductionmentioning
confidence: 99%